2021
DOI: 10.1101/2021.06.16.448624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico Computed Clusters of Prostate Luminal Progenitors Match FACS-Enriched LSCmed cells

Abstract: Several groups recently published single-cell (sc) expression atlases of the adult mouse prostate cells based on RNA sequencing (scRNA-seq) data. All studies identified one computerized cluster of non-secretory luminal progenitor cells enriched in luminal and stemness-related gene transcripts. The actual correspondence between these luminal progenitor cell clusters has not been investigated. In addition, the presence of Krt4 (encoding cytokeratin 4) in these in silico-identified luminal progenitors suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Strikingly, several of them, including the LSC med cell marker Krt4, were previously identified in the 111-gene mouse LSC med cell signature 31 (TaBle 3). Accordingly, a significant enrichment of the latter signature was observed in each scRNA-seq dataset for the sole population identified as luminal progenitor cells 50 (Fig. 2a-d).…”
Section: Single-cell Profilingmentioning
confidence: 81%
See 4 more Smart Citations
“…Strikingly, several of them, including the LSC med cell marker Krt4, were previously identified in the 111-gene mouse LSC med cell signature 31 (TaBle 3). Accordingly, a significant enrichment of the latter signature was observed in each scRNA-seq dataset for the sole population identified as luminal progenitor cells 50 (Fig. 2a-d).…”
Section: Single-cell Profilingmentioning
confidence: 81%
“…In the past 3 years, several single-cell RNA sequencing (scRNA-seq) studies of healthy mouse prostates have provided unprecedented evidence that the molecular diversity of the prostate epithelium far exceeds the classical histological description [32][33][34][35][36] . Despite the largely different number of cells sequenced in each scRNA-seq study 50 , a unique cluster of basal cells was identified in all of them, suggesting a relative molecular homogeneity. By contrast, luminal cell heterogeneity ranged from three to six distinct clusters (TaBle 2), which most probably reflects methodological differences in bioinformatic processes (for example, parameters used for cell clustering).…”
Section: Single-cell Profilingmentioning
confidence: 95%
See 3 more Smart Citations